Investigation of free-living honey bee colonies in Ireland. Issue 2 (30th October 2020) - Browne, Keith A.; Hassett, Jack; Geary, Michael; Moore, Elizabeth; Henriques, Dora; Soland-Reckeweg, Gabriele; Ferrari, Roberto; Mac Loughlin, Eoin; O'Brien, Elizabeth; O'Driscoll, Saoirse; Young, Philip; Pinto, M. Alice; et al.
Abstract : Apis mellifera mellifera (Linnaeus), the Western European honey bee, is considered extinct in the wild over most of its range due largely to hybridisation and replacement by other subspecies, parasitism by Varroa destructor, habitat loss, and effects from agricultural pesticides. The purity of the subspecies within the managed cohort is also at risk over much of its range. Here, we investigated if honey bee colonies inhabited locations outside of the apiaries. In those we located, we explored how long the colony persisted and we investigated the genotypes of the bees using multiple markers. We show here that unmanaged free-living honey bee colonies are present and widespread in Ireland, inhabiting a mixture of nesting habitats with some colonies persisting naturally and unaided over multiple years. Molecular data including mitochondrial, microsatellite, and SNPs evidence indicate that the free-living population sampled is largely comprised of pure A. m. mellifera . Finally, we discuss the implications of conserving free-living A. m. mellifera in Ireland and its possible role in improving the fitness of the managed population both in Ireland and the rest of its European range.